Direct imaging of hyperpolarized 129Xe alveolar gas uptake in a mouse model of emphysema. Issue 1 (8th August 2012) - Iguchi, Satoshi; Imai, Hirohiko; Hori, Yuki; Nakajima, Junichi; Kimura, Atsuomi; Fujiwara, Hideaki
Abstract MRI of hyperpolarized 129Xe dissolved in pulmonary tissues, and blood has the potential to offer a new tool for regional evaluation of pulmonary gas exchange and perfusion; however, the extremely short T 2*<inline-graphic xlink:href="ark:/27927/pgg22frch85" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and low magnetization density make it difficult to acquire the image. In this study, an ultrashort echo‐time sequence was introduced, and its feasibility to quantitatively assess emphysema‐like pulmonary tissue destruction by a combination of dissolved‐ and gas‐phase 129Xe lung MRI was investigated. The ultrashort echo‐time has made it possible to acquire dissolved 129Xe images with reasonably high spatial resolution of 0.625 × 0.625 mm2 and to obtain T 2*<inline-graphic xlink:href="ark:/27927/pgg22frch4z" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> of 0.67 ± 0.30 ms in a spontaneously breathing mouse at 9.4 T. The regional dynamic alveolar gas uptake as well as subsequent transport by pulmonary blood flow was also visualized. The ratio of 129Xe magnetization that diffused into the septa relative to the gas‐phase magnetization F was regionally evaluated. The mean F value of elastase‐treated mice was 2.28 ± 0.46%, which was significantly reduced from that of control mice 3.41 ± 0.48% (P = 0.0052). This reflects the reduced uptake efficiency due to alveolar tissue destruction and is correlated with the histologically derived alveolar surface‐to‐volume ratio. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.